Analisis Keberhasilan Prosedur Inseminasi Intrauterin bagi para Pasangan dengan Penyebab Infertilitas yang Tidak Diketahui - Yeuis Diah Sri Lestari; Azniah Syam (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Unexplained infertility remains a significant clinical challenge, defined by the inability to conceive despite normal findings in standard fertility evaluations, including ovulation, tubal patency, and semen analysis. Intrauterine insemination (IUI) has emerged as a preferred first-line treatment for these cases due to its minimally invasive procedure, cost-effectiveness, and ease of administration. This study aims to evaluate the effectiveness of IUI in improving pregnancy outcomes among couples with unexplained infertility through a comprehensive literature review spanning the last ten years. A total of 20 peer-reviewed articles were analyzed, sourced from PubMed, Scopus, and Google Scholar. The selection criteria included full-text availability, English language, and direct relevance to IUI and unexplained infertility. The review encompassed randomized controlled trials, cohort studies, observational research, and meta-analyses. The majority of studies reported positive outcomes, particularly when IUI was combined with ovulation induction agents such as letrozole or clomiphene citrate. Notably, pregnancy success rates were highest during the first three cycles of IUI treatment. Several factors were identified as key predictors of IUI success, including maternal age under 35 years, the presence of multiple mature follicles, optimal endometrial thickness, and good sperm parameters. Additionally, the psychological and emotional support provided to couples undergoing IUI played a role in treatment adherence and outcome satisfaction. In conclusion, IUI represents an effective and pragmatic initial treatment for couples with unexplained infertility, especially when guided by individualized protocols and clinical indicators. Proper patient counseling and realistic expectations regarding success rates are essential. Further studies are recommended to explore long-term outcomes, cost-benefit ratios, and comparative effectiveness with other fertility treatments such as in vitro fertilization (IVF).